Modernization of Islamic Thought Amidst the Challenges of Radicalism and Secularism - Kadir, Surni; Abd. Rasyid, Nurhayati; Rudji, Hamdi; Kamal, Kamal (Seutia Hukamaa Cendekia, 2025)
This article discusses the modernization of Islamic thought as a response to the increasingly complex challenges of radicalism and secularism in the contemporary era. Modernization in Islamic thought aims to align religious principles with the dynamics of developments in the era without sacrificing the core values of Islam. On the one hand, radicalism emerges as a movement that rejects all forms of change and modernity, often using the pretext of religion to legitimize violence and intolerance. On the other hand, secularism offers an approach that separates religion from public life, thus potentially reducing the role of spirituality in the social order. Through literature analysis and case studies in several Muslim countries, this article explores the strategy of modernizing Islamic thought that can be a middle ground between the two extremes. The results of the study indicate that the modernization of Islamic thought must be based on a deep understanding of classical texts, accompanied by contextualization according to the social and cultural needs of today's society. In addition, collaboration between Muslim intellectuals and traditional scholars plays an important role in spreading a moderate, inclusive, and relevant understanding of Islam. In conclusion, the modernization of Islamic thought can be an effective solution in bridging the need to adapt to global change without ignoring the essence of Islamic teachings, while at the same time countering the threats of radicalism and secularism. This research contributes to the development of moderate Islamic discourse that is appropriate to the modern socio-political context.